5m+3n-2m-8n=

Simple and best practice solution for 5m+3n-2m-8n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m+3n-2m-8n= equation:


Simplifying
5m + 3n + -2m + -8n = 0

Reorder the terms:
5m + -2m + 3n + -8n = 0

Combine like terms: 5m + -2m = 3m
3m + 3n + -8n = 0

Combine like terms: 3n + -8n = -5n
3m + -5n = 0

Solving
3m + -5n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5n' to each side of the equation.
3m + -5n + 5n = 0 + 5n

Combine like terms: -5n + 5n = 0
3m + 0 = 0 + 5n
3m = 0 + 5n
Remove the zero:
3m = 5n

Divide each side by '3'.
m = 1.666666667n

Simplifying
m = 1.666666667n

See similar equations:

| (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= | | 25c^2-121g^2=0 | | Y=3/4x-9;(-8,-18) | | 4y+10=-26 | | (14x+5)+(10x+15)=80 | | 6x+10=9x-11 | | 8n-3=15+2n | | 6y-9=45 | | 3/1*(8X/7-9/7) | | 3/1*(8X-9/7) | | 12x^3+6x^2-5x-3=0 | | 2m^2+9m+17=8 | | 3x+6-2=10 | | X+3+x+x-4x-4=6x-20 | | abs(2*x-5)=7 | | 5=S+4 | | -27+x=x+29 | | 3x+2y=3x-4 | | X+[x+24]=52 | | -2(d-4)=12 | | (4x+5)-(3x)= | | 7x-18=x+11 | | (7n-2)(5n-4)= | | 2x+7854.5=50000 | | 5(2x-10)= | | 15(v+2)-3v=3(4v+3)-14 | | (1/x^2)=95 | | 20x^3-1=0 | | (x+6)(8x-1)=0 |

Equations solver categories